What is the Best Way to Diagnose Possible Asthma Patients with Negative Bronchodilator Reversibility Tests? - Başa Akdoğan B; Koca Kalkan I; Köycü Buhari G; Özdedeoğlu Ö; Ateş H; Aksu K; Öner Erkekol F (Journal of Asthma and Allergy, 2024)
Buket Başa Akdoğan, Ilkay Koca Kalkan, Gözde Köycü Buhari, Özlem Özdedeoğlu, Hale Ateş, Kurtuluş Aksu, Ferda Öner Erkekol Department of Chest Diseases, Division of Immunology and Allergy, University of Health Sciences Ataturk Chest Diseases and Chest Surgery Education and Research Hospital, Ankara, TurkeyCorrespondence: Buket Başa Akdoğan, Department of Chest Diseases, Division of Immunology and Allergy, University of Health Sciences Ataturk Chest Diseases and Chest Surgery Education and Research Hospital, Incirlist, No: 57 Floor:3, 34147 Bakirkoy/Istanbul, Ankara, Turkey, Tel +90 5053518861 ; +90 850 4339393, Email drbuketakdogan@yahoo.comObjective: The best method and strategy for the diagnosis of asthma remains unclear, especially in patients with negative bronchodilator reversibility test (BDRT). In our study, we aimed to investigate the diagnostic yield of peak expiratory flow (PEF) variability for this patient group.Methods: A total of 50 patients with suspected asthma, all with negative BDR test, were included in the study. Demographic information and symptoms were recorded and PEF variability was monitored for 2 weeks. Metacolinbronchial provocation test (mBPT) was performed. Asthma was diagnosed when PEF variability ≥ 20% and/or positive mBPT was observed.Results: 30 of 50 patients were diagnosed with asthma. After 1 month, 17 patients were evaluated for treatment outcomes. The sensitivity and specificity of PEF variability for different cut-off values (≥ 20%, > 15% and > 10%) were 61.5– 83.3, 88.5– 62.5 and 100– 16.7, respectively. One of the most important findings of our study was the absence of variable airflow limitation or airway hyper reactivity in 39% patients with a previous diagnosis of asthma. Multiple logistic regression analysis revealed that a low baseline FEF25-75 value was an independent predictive factor for the diagnosis of asthma (p= 0.05).Conclusion: The most efficient diagnostic test for asthma is still unclear due to many factors. Our study is one of the few studies on this subject. Although current diagnostic recommendations generally recommend a PEF variability of 10% for the diagnosis of asthma, this threshold may not be appropriate for the BDR-negative patient group. Our results suggest using a threshold value of < 15% for PEF variability when excluding asthma and ≥ 20% when confirming the diagnosis of asthma in patients with clinically suspected but unproven reversibility. Furthermore, FEF25-75 is considered to be an important diagnostic parameter that should be included in diagnostic recommendations for asthma.Keywords: diagnosis of asthma, reversibility, peak expiratory flow (PEF) variability, bronchial challenge test, forced expiratory flow (25-75%)